‘Soft’ forms of direct democracy: Explaining the occurrence of referendum motions and advisory referendums in Finnish local government - Maija Jäske (John Wiley & Sons Ltd., 2022)
This study investigates ‘soft’ forms of direct democracy and identifies factors that explain their occurrence. Soft direct democracy refers to non-binding referendum motions and advisory referendums, which the literature on direct democracy has largely ignored. Strategic motives have dominated previous explanations of the occurrence of initiatives and referendums, but are less useful in exploring non-binding procedures of direct democracy. The article distinguishes four types of factors – socio-structural, party system, political support and learning – and tests hypotheses on their effects with sub-national data from Finland. The data enable us to compare two different types of instruments – non-binding referendum motions and advisory referendums – while controlling for many unobserved factors. The findings show that erosion of political support, participatory traditions and policy diffusion explain the occurrence of bottom-up referendum motions, while the last two together with small population and party system factors predict the occurrence of advisory government-initiated referendums.